ЕКОЛОГІЯ ТА ОХОРОНА НАВКОЛИШНЬОГО СЕРЕДОВИЩА ЯК ОБ’ЄКТИ ЗВІТНОСТІ: СУЧАСНИЙ СТАН ТА ПІДХОДИ ДО УДОСКОНАЛЕННЯ - Polishchuk, Iryna; Laichuk, Svitlana; Yeliseev, Volodymyt; Mostipaka, Iryna (Zhytomyr Ivan Franko State University, 2022)
The article is devoted to the comparative characteristics of statistical reporting on the environment and environmental aspects of the Management Report. It was found that the Management Report, unlike statistical reporting, does not have a regulated list of indicators. It is not possible to identify the relationship between the indicators of statistical reporting and the Management Report, as individual statistics on individual enterprises are not published, only consolidated statistical information is disclosed. The management report characterizes the development strategy of the enterprise and may contain information of a descriptive nature. It was found that the users of statistical information on the environment are the State Statistics Service of Ukraine, public authorities and local governments, society, NGOs, environmental protection institutions, research and educational institutions, social and demographic institutions, etc. An algorithm for regulating the preparation of the Management Report for enterprises in accordance with the Law of Ukraine "On Accounting and Financial Reporting in Ukraine" has been developed. A comparative description of financial and non-financial indicators in terms of environmental aspects of the published Reports on the management of domestic enterprises by different types of economic activity. It is proposed in the Report on the management of large and medium-sized enterprises, in terms of environmental aspects, to disclose the following indicators: the volume of waste by hazard class; volumes of electricity consumption; volumes of water consumption for own and economic purposes; volumes of fuel consumption for transport needs; capital investments in the implementation of environmental measures; current costs for the implementation of environmental measures; environmental tax and resource intensity indicators. We consider it expedient to publish information on the planned list of environmental measures, the degree of their implementation, as well as current and capital expenditures incurred for their implementation, the results achieved to improve the environment.